Factors Affecting Conduct of Practical Activities in Science Subjects in Some Selected Secondary Schools in Tarauni Local Government Area, Kano State - Ado, A.S.; Hussain, S.A.; Muzammil, M.; Gwarzo, F.S. (International Journal of Scientific Research in Biological Sciences, 2022)
Developing scientifically literate individuals who are highly competent in logical thought and action is the main objective of science education. The objectives of science education in Nigeria include preparing students to observe and explore their surroundings, to explain basic natural phenomena, to develop scientific attitudes. In the study, 291 students from 10 secondary schools in the Tarauni local government area of Kano state were purposefully selected. The study identified factors related to teachers, laboratory-related factors, and learners` perceptions of factors influencing the conduct of practical activities using a descriptive survey research design. Data from the respondents was gathered using instrument titled Factors Affecting Conduct of Practical in Science Questionnaire (FACPSQ). Descriptive statistics (frequencies and percentages) were used to analyse the data obtained. The findings indicated that teacher-related factors that affect how science practical are conducted include lack of management motivation and awareness, full-time occupancy of science teachers, low commitment from teachers to practical classes, teacher absenteeism, teachers` lack of knowledge about practical work and low qualifications for science teachers and laboratory attendants. Findings showed that inadequate laboratory equipment, inadequate time assigned for practical activities, a lack of practical textbooks, an incompetent lab assistant, and inefficient instrument maintenance were laboratory-related factors that significantly impacted practical activities in science. The result also demonstrated those students` perceptions that affected scientific practical included: more students than equipment; a hazardous laboratory atmosphere; and a lab assistant who lacked motivation. Based on the findings, teachers-related factors, laboratory-related factors, and students` attitudes toward laboratory activities all have an impact on how science practical activities are carried out. The study suggested that, in order to ensure that practical work is carried out effectively, practical time should be allotted on the school schedule, and regular classroom monitoring should be carried out. There should be enough basic necessities on hand. Additionally, science teachers must carefully plan adaptive teaching methods for their students that will stimulate their interest in learning science and help them apply what they have learned to meet societal requirements.